The Productivity Consequences of Political Turnover: Firm-Level Evidence from Ukraine's Orange Revolution - John S. Earle; Scott Gehlbach (Institute for the Study of Labor (IZA), 2014)
We examine the impact of political turnover on economic performance in a setting of largely unanticipated political change and profoundly weak institutions: the 2004 Orange Revolution in Ukraine. Exploiting census-type panel data on over 7,000 manufacturing enterprises, we find that the productivity of firms in the regions most supportive of Viktor Yushchenko increased by more than 15 percentage points in the three years following his election, relative to that in the most anti-Yushchenko regions. We conclude that this effect is driven primarily by particularistic rather than general economic policies that disproportionately increased output among large enterprises, government suppliers, and private enterprises three types of firms that had much to gain or lose from turnover at the national level. Our results demonstrate that political turnover in the context of weak institutions can have substantial distributional effects that are reflected in economic productivity.
Keywords: H32; D72; P26; 330; political connections; firm behavior; voting; transition